The business of leisure : tourism history in Latin America and the Caribbean - Wood, Andrew Grant, 1958- (University of Nebraska Press, 2021)
The essays in this collection explore the history of tourism and its promotion and development throughout Latin American and the Caribbean in the twentieth century.